Satisfacción anestésica del paciente sometido a cirugía electiva en el HGR1 IMSS Morelia - Vega Munguía, Jalil Alejandro (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Background: A priority of health units is the care of the population under their care. Preanesthetic assessment allows resources to be optimized for the patient's well-being. The opinion of patients is an indicator that allows assessing the level of use of medical services with the purpose of preparing them both physically and psychologically to face surgical trauma in the hope of improving and/or correcting the pathology presented by it. Objective: Determine the level of anesthetic satisfaction in the patient undergoing elective surgery at the Regional General Hospital No 1. IMSS Morelia, Michoacán. Material and methods: It is an observational, cross-sectional and descriptive study. It was performed on patients undergoing elective surgery at the Regional General Hospital No 1 IMSS, Morelia Michoacán. They were evaluated in the hospitalization area once they had left the operating room. By applying the IOWA Anesthetic Satisfaction scale. Consisting of 11 reagents. With a Cronbach's alpha validation of 0.8, completion time of 4.6+/-2.1 min, response rate of 92%. Descriptive statistical analysis was performed: measures of central tendency, simple frequencies and bivariates. Carried out under informed consent. Results: The study population was 124 patients, of which 58.9% were men, average age was 34.7 years, the most frequent treating service was General Surgery (33.9%), and the most frequent anesthetic technique recorded is the regional one, representing 51.6%, when sizing our variables, we found “total patient satisfaction” as a result. Conclusions: Patients undergoing elective surgery at the HGR1 IMSS Morelia are “totally satisfied” with their anesthetic care. We can highlight that there are factors such as nausea, feeling cold or hot during surgery that modify the patient's feeling of satisfaction.

Antecedentes: Una prioridad de las unidades de salud es el cuidado de la población a su cargo. La valoración preanestésica permite optimizar recursos en pro del bienestar del paciente. La opinión de los pacientes es un indicador que permite valorar el nivel de utilización de los servicios médicos teniendo como finalidad de prepararlo tanto de manera física y psicológica para enfrentar el trauma quirúrgico en espera de mejorar y/o corregir la patología presentada por el mismo. Objetivo: Determinar el nivel de satisfacción anestésica en el paciente sometido a cirugía electiva en el Hospital General Regional No 1. IMSS Morelia, Michoacán. Material y métodos: es un estudio observacional, transversal y descriptivo. Se realizó en pacientes intervenidos quirúrgicamente de manera electiva en el Hospital General Regional No 1 IMSS, Morelia Michoacán. Fueron evaluados en el área de hospitalización una vez egresados del área de quirófano. Mediante la aplicación de la escala de IOWA de Satisfacción Anestésica. Constando de 11 reactivos. Contando con una validación alfa de Cronbach de 0.8, tiempo de realización de 4.6+/-2.1 min, tasa de respuesta del 92%. Se realizó análisis estadístico descriptivo: medidas de tendencia central, frecuencias simples y bivariados. Realizado bajo consentimiento informado. Resultados: La población de estudio fue de 124 pacientes, de los cuales el 58.9% eran hombres, media de edad fue de 34.7 años, el servicio tratante más frecuente fue Cirugía general (33.9%), y la técnica anestésica más frecuente registrada es la regional representando 51. 6%, al dimensionar nuestras variables encontramos como resultado “satisfacción total del paciente”. Conclusiones: Los pacientes sometidos a cirugía electiva en el HGR1 IMSS Morelia se encuentran “totalmente satisfechos” con su atención anestésica podemos destacar que hay factores como las náuseas, sentir frio o calor durante la cirugía que modifican la sensación de satisfacción del paciente.
Facultad de Ciencias Médicas y Biológicas. Instituto Mexicano del Seguro Social. Especialidad en Anestesiología
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18784; info:eu-repo/classification/cti/3; FCMB-R-E-2024-0306; Anestesia; Malestar; Daño